Philological Quarterly, State University of Iowa, Iowa City, vol. XXV, 1946. - Boyd-Bowman, Peter (Nueva Revista de Filología Hispánica (NRFH), 1950)
Se reseñó: Philological Quarterly, vol. XXV, 1946.